On the Role of the Head Ganglia in Posture and Walking in Insects - Emanuel, Stav; Kaiser, Maayan; Pflueger, Hans-Joachim; Libersat, Frederic (Frontiers in Physiology, 2020)
In insects, locomotion is the result of rhythm generating thoracic circuits and their modulation by sensory reflexes and by inputs from the two head ganglia, the cerebral and the gnathal ganglia, which act as higher-order neuronal centers playing different functions in the initiation, goal-direction and maintenance of movement. Current knowledge on the various roles of major neuropiles of the Cerebral Ganglia, such as Mushroom bodies and the Central Complex, in particular, are discussed as well as the role of the Gnathal Ganglia. Thoracic and head ganglia circuitries are connected by ascending and descending neurons. While less is known about the ascending neurons, recent studies in large insects and Drosophila have begun to unravel the identity of descending neurons and their appropriate roles in posture and locomotion. Descending inputs from the head ganglia are most important in initiating and modulating thoracic central pattern generating circuitries to achieve goal directed locomotion. In addition, the review will also deal with some known monoaminergic descending neurons which affect the motor circuits involved in posture and locomotion. In conclusions, we will present a few issues that have, until today, been little explored. For example, how and which descending neurons are selected to engage a specific motor behavior and how feedback from thoracic circuitry modulate the head ganglia circuitries. The review will discuss results from large insects, mainly locusts, crickets and stick insects but will mostly focus on cockroaches and the fruit fly, Drosophila.